(untitled) (Archives of Pediatrics of Uruguay, 2025)
Dengue is a viral disease transmitted by the Aedes aegypti mosquito. This infection has shown a global increase in cases, particularly affecting the Americas region. In Uruguay, the most recent outbreak (2024) recorded 702 autochthonous and 410 imported cases, underscoring the need to strengthen surveillance and management strategies. Dengue can complicate pregnancy with risks of preterm birth and low birth weight, although a statistically significant association has not been confirmed. The risk of vertical transmission ranges from 1.6-10.5%, increasing if the infection occurs close to delivery. Newborns can acquire the infection vertically (trans-placentally) or horizontally (mosquito bite). A wide variability in clinical presentation can be observed, ranging from asymptomatic patients, mild symptoms, or severe cases with potential mortality, requiring differential diagnosis with sepsis. Recommended tests include PCR in cord blood, NS1 antigen detection, and IgM, adapted to the clinical timing. Breastfeeding is safe and recommended in all cases, even for infected mothers, given its protective role. These recommendations aim to optimize the identification and management of at-risk neonates, ensuring a comprehensive and preventive approach to dengue.